Challenges and Opportunities for Historical and Cultural Tourism Development in Macanputih Village - Rizky, Nurul Lutfiyana; Hariyati, Gea Supri; Hikayah, Nur; Salsabila, Shofi (CV. Sekawan Siji, 2025)
This article aims to examine the development of village tourism destinations and historical and cultural tourism in Indonesia, and identify its success factors. The methods used include literature study and historiographic approach to reconstruct the history and potential of tourism villages, as well as qualitative analysis through interviews and source criticism related to tourism development in Macanputih Village. The results showed that the success of tourist destination development was influenced by community strengthening, provision of adequate facilities and infrastructure, and effective management of local resources. The development of historical and cultural tourism in the village has great potential, especially through digital promotion and innovation in history learning. The discussion emphasises the importance of sustainable development based on Tri Hita Karana principles and collaboration between the government, community and private sector to maintain the sustainability of the village environment and culture.